2020
DOI: 10.1016/j.bbamem.2019.183152
|View full text |Cite
|
Sign up to set email alerts
|

Detergent-free extraction of a functional low-expressing GPCR from a human cell line

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 71 publications
1
29
0
Order By: Relevance
“…The regenerated samples were stable and soluble for days at room temperature. These results highlight the ability of SMALPs to efficiently extract this model GPCR in a stable form from its native, mammalian tissue, as has been done in cell lines and lower species with other GPCRs (Jamshad et al, 2015;Gakhar et al, 2020;Ganapathy et al, 2020;Bada Juarez et al, 2020;Routledge et al, 2020;Ueta et al, 2020).…”
Section: Smalp-encapsulated Abca4 and Rhodopsin Retain Ligand Bindingmentioning
confidence: 61%
“…The regenerated samples were stable and soluble for days at room temperature. These results highlight the ability of SMALPs to efficiently extract this model GPCR in a stable form from its native, mammalian tissue, as has been done in cell lines and lower species with other GPCRs (Jamshad et al, 2015;Gakhar et al, 2020;Ganapathy et al, 2020;Bada Juarez et al, 2020;Routledge et al, 2020;Ueta et al, 2020).…”
Section: Smalp-encapsulated Abca4 and Rhodopsin Retain Ligand Bindingmentioning
confidence: 61%
“…In all cases of GPCR solubilisation by SMA, some degree of receptor functionality in SMA lipid-nanoparticles has been demonstrated. For the A 2A R and D 1 R, radioligand binding assays produced similar ligand binding profiles in both the original membranes and in the SMA-solubilised material (Jamshad et al 2015a;Bada Juarez et al 2020). Subsequent publications using A 2A R-SMALPs have also demonstrated ligand binding using fluorescence correlation spectroscopy (Grime et al 2020) and conformational changes in the receptor caused by inverse agonist binding (Routledge et al 2020), although in the latter case limited changes were observed upon agonist binding.…”
Section: Polymer Lipid Nanoparticlesmentioning
confidence: 81%
“…The dopamine D1 receptor is expressed at low levels in HEK cells and has been purified using SMA(3:1) copolymer. Once stably integrated in native nanodiscs, this GPCR is helical based on circular dichroism (CD) spectra, and binds the SCH23390 antagonist and neurotensin peptide based on radioligand and microscale thermophoresis (MST) assays [ 40 ]. The dopamine and ghrelin receptors form heteromultimeric complexes in hypothalamic neurons.…”
Section: Native Gpcr–lipid Complexesmentioning
confidence: 99%